Antimicrobial activity of ceftazidime/avibactam, ceftolozane/tazobactam and comparator agents against Pseudomonas aeruginosa from cystic fibrosis patients. Issue 3 (4th September 2021) - Sader, Helio S; Duncan, Leonard R; Doyle, Timothy B; Castanheira, Mariana
Abstract: Objectives: To evaluate the antimicrobial susceptibility patterns of Pseudomonas aeruginosa isolates collected from the lower respiratory tract of cystic fibrosis (CF) patients. Methods: We susceptibility tested 273 contemporary P. aeruginosa isolates from 39 hospitals worldwide (17 countries) by the reference broth microdilution method. Results: Ceftazidime/avibactam [MIC50/90, 2/8 mg/L; 96.0% susceptible (S)] was the most active agent, followed by ceftolozane/tazobactam (MIC50/90, 1/4 mg/L; 90.5% S), ceftazidime (MIC50/90, 2/>32 mg/L; 80.6% S), piperacillin/tazobactam (MIC50/90, 4/128 mg/L; 80.2% S) and tobramycin (MIC50/90, 2/>16 mg/L; 76.6% S). Ceftazidime/avibactam retained activity against P. aeruginosa isolates non-susceptible to meropenem (86.5% S to ceftazidime/avibactam), piperacillin/tazobactam (85.2% S to ceftazidime/avibactam) or ceftazidime (79.2% S to ceftazidime/avibactam). MDR phenotype was observed among 36.3% of isolates, and 88.9% and 73.7% of MDR isolates were susceptible to ceftazidime/avibactam and ceftolozane/tazobactam, respectively. Against isolates non-susceptible to meropenem, piperacillin/tazobactam and ceftazidime, susceptibility rates were 78.9% for ceftazidime/avibactam and 47.4% for ceftolozane/tazobactam. Ceftazidime/avibactam was active against 65.4% of ceftolozane/tazobactam-non-susceptible isolates and ceftolozane/tazobactam was active against 18.2% of ceftazidime/avibactam-non-susceptible isolates. Conclusions: Ceftazidime/avibactam and ceftolozane/tazobactam exhibited potent and broad-spectrum activity against P. aeruginosa isolated from CF patients worldwide, but higher susceptibility rates for ceftazidime/avibactam compared with ceftolozane/tazobactam were observed among the resistant subsets. Ceftazidime/avibactam and ceftolozane/tazobactam represent valuable options to treat CF pulmonary exacerbations caused by P. aeruginosa .